The Determinants of Bank Default Risk: Evidence from Commercial Banks in the United States from 2011-2017 - FANG, JIE (2018)
This study aims to detect the determinants of default risk of commercial banks in the United States from 2011-2017. In this period, the U.S. economy has been boomed during the last few years, the Federal Reserve has continued to cut interest rates to stimulate economic development. On the other hand, the newly appointed Trump administration advocates weakening financial regulation to further stimulate economic development and stimulate the vitality of financial markets. However, excessively weakening regulation and loosening financial regulation may cause the US banking industry to once again enter speculation. Therefore, this paper collects macro and microdata of the US banking industry from 2011 to 2017 and makes a detailed analysis and forecast of bank bankruptcy risk based on the actual financial market situation. The regression results show that the macroeconomic impact on bank bankruptcy risk is very significant. Among them, GDP growth, inflation rate, interest rate and unemployment rate all show a positive correlation with bank bankruptcy risk. Bank special areas, bank size and loan loss provision show a correlation with bankruptcy risk.